2023
DOI: 10.1101/2023.06.27.546744
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Self-extinguishing relay waves enable homeostatic control of human neutrophil swarming

Abstract: Neutrophils exhibit self-amplified swarming to sites of injury and infection. How swarming is controlled to ensure the proper level of neutrophil recruitment is unknown. Using an ex vivo model of infection, we find that human neutrophils use active relay to generate multiple pulsatile waves of swarming signals. Unlike classic active relay systems such as action potentials, neutrophil swarming relay waves are self-extinguishing, limiting the spatial range of cell recruitment. We identify an NADPH-oxidase-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“… 36 Previous work has shown that the activity of NADPH oxidase and ROS signaling are dispensable for initiating neutrophil swarming. 13 , 16 , 18 Based on the use of neutrophils from NADPH oxidase-deficient chronic granulomatous disease (CGD) patients in these studies, ROS production appears to emerge as a control mechanism to avoid over-recruitment of neutrophils at late stages of swarming. However, none of these studies have pinpointed the sources of ROS production in populations of swarming neutrophils.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… 36 Previous work has shown that the activity of NADPH oxidase and ROS signaling are dispensable for initiating neutrophil swarming. 13 , 16 , 18 Based on the use of neutrophils from NADPH oxidase-deficient chronic granulomatous disease (CGD) patients in these studies, ROS production appears to emerge as a control mechanism to avoid over-recruitment of neutrophils at late stages of swarming. However, none of these studies have pinpointed the sources of ROS production in populations of swarming neutrophils.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have used these controllable swarming devices for the functional characterization of human neutrophils from the blood of patients with different disease backgrounds. 9 , 16 , 17 , 18 , 19 Furthermore, technical adaptations now also allow the study of neutrophil swarming in response to patterned arrays of living microbes, in particular different species of living fungi. 18 , 20 , 21 , 22 Thus, recent developments of swarming-on-a-chip platforms have brought forward versatile applications for the study of primary human and mouse neutrophils, but also neutrophil-like cell lines.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 21 , 43 , 44 The subsequent recruitment of macrophages leads to swarm resolution, making this a transient process 44 , 45 with the LTB 4 amplification loop ultimately self-limited by NADPH oxidase activity. 46 LTB 4 signaling appears to be heightened in CGD, where loss of NADPH oxidase activity fails to inhibit the production of LTB 4 46 and cell aggregation results in the heightened transcellular production of LTB 4 . 47 LTB 4 is of particular importance in innate responses to fungal pathogens generally 47 , 48 , 49 , 50 and, in CGD mice, has been shown to be the key chemoattractant for early neutrophil recruitment following zymosan installation and the initiator of bone marrow neutrophil aggregation.…”
Section: Discussionmentioning
confidence: 99%